THE EFFECTIVENESS OF GUIDED WRITING TO TEACH RECOUNT TEXT - Risma Rahajeng Lestari (Universitas Islam Sumatera Utara, 2019)
This study aims to measure the effectiveness of using guided writing in teaching the 2017/2018 10th grade MA DarulUlum Ngabar recount text. This study used a pre-experimental study design with a quantitative approach. The subjects of this survey were 10th graders of MA Darul Ulum Ngabar, with a total of 30 students. The research equipment was carried out through a written test. Meanwhile, a method of collecting data from pre-treatment and post-treatment pre-test results using guided writing. The data analysis method for this study is statistical analysis of t-test data. Based on the results of the data analysis, the student pre-test results showed an average score of 75.16 and the student post-test results averaged 82.5. The results of data analysis showed that the value was 5.384 and the table was 2.045 at a significant level of 5%. It can be concluded as follows: t-valuet- table thus, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Therefore, there was significant difference in the increase of pre-test and post-test results in teaching writing using guided writing is effective for students of grade 10 MA Darul Ulum Ngabar in the academic year 2017/2018.